Examining the policy-practice gap- The issue of crop burning induced Particulate Matter pollution in Northwest India. Issue 1 (16th December 2020) - Kaushal, Leena Ajit
ABSTRACT: The study examine the efficacy of government policy interventions initiated since 2014 to curb FCRB in NW Indian states and the related air pollution in Delhi-NCR during 2014-2019. The regression analysis suggests an increase in PM2.5 of 69 µg/m3/1000 surge in fires. VIIRS retrieved data suggest an overall declining trend of 1606 and 4308 fire counts per year across NW states during October-November respectively. The monthly PM2.5 concentrations in New Delhi exhibits a decline of 2.18 µg/m3 and 5.17 µg/m3 per year over the same period. Despite an overall increase of 17.6 % rice productivity, a noted decrease in fire activity over the period is an encouraging move, likely a result of some control imposed by authorities on FCRB. Owing to a significant 35.5% rise in wheat productivity, data records rising trend in wheat residue burning activities in April ( 1298/year) and May ( 2402/year) but do not trigger extreme pollution due to difference in intensity of fires across harvesting seasons and relatively weak northwesterly wind direction. Nevertheless, the overall high PM2.5 levels in October-November and April-May compared to NAAQS 24-hour average of 60µg/m3, disproves the overall efficacy of government policies to curb FCRB and related air pollution in IGP region.